Italy's divided memory - Foot, John 1964- (Italian and Italian American studies, 2009)
Divided memory : theory, methodology, practice -- World War I : monument wars, unknown soldiers, and open-air cemetries -- Fascist memories, memories of fascism -- Italian wartime camps, Italians in wartime camps : traces, memories, silences, 1940-2008 -- 1940-1943 : victory, occupation, defeat, collapse, memory -- Nazi massacres and divided memory : stories, causes, scapegoats, memoryscapes -- The resistance : three wars, many memories, many silences -- The strategy of tension and terrorism : Piazza Fontana and "the Moro case" -- Conclusion: End of the voyage : facts, memory, history